Analysis of the syngenesis pioneer stage on the iron ore enterprises dump sites in the Kostanay region - Simanchuk, Ye.A.; Kuprijanov, А.N.; Sultangazina, G.J. (Fundamental and Experimental Biology, 2023)
Study of primary stages of syngenesis at the dumps of the Sokolovsko-Sarbai Mining and Processing Production Association, including Sokolovsky, Sarbaisky, Kacharsky deposits was carried out. In total, during the study, 63 geobotanical descriptions were compiled; pioneer grouping being found in 15 of them. Waste and poor rocks of iron ore open pits dumps are difficult to demutate during first few years after backfilling completion, therefore, succession initial stage here proceeds extremely slowly. However, succession rate gradually increases as the edaphic conditions of the ecotype improve and phyto-environment develops. Moreover, during the study, division of soils into saline and non-saline ones was discovered, establishing that this factor greatly influenced projective cover and species composition of the pioneer plants discovered. Floristic data were processed using IBIS 7.2 program developed by Zverev. Qualitative and quantitative accounting of plants was carried out in accordance with generally accepted botanical methods, during the application of which such parameters as occurrence, general and partial projective cover were noted. It was ascertained that on saline soils halophytes and weedy species with wide ecological amplitude predominate, while on non-saline ones different types of wormwood are most stable. All species on the dumps with non-saline substrates show wide ecological amplitude.